Synthesis, structural and electrochemical properties of V4O9 cathode for lithium batteries - Senguttuvan, Premkumar; Lee, Eungje; Key, Baris; Johnson, Christopher S. (Frontiers in Chemistry, 2023)
Single-phase three-dimensional vanadium oxide (V4O9) was synthesized by reduction of V2O5 using a gas stream of ammonia/argon (NH3/Ar). The as-synthesized oxide, prepared by this simple gas reduction method was subsequently electrochemically transformed into a disordered rock salt type-“Li3.7V4O9” phase while cycling over the voltage window 3.5 to 1.8 V versus Li. The Li-deficient phase delivers an initial reversible capacity of ∼260 mAhg−1 at an average voltage of 2.5 V vs. Li+/Li0. Further cycling to 50 cycles yields a steady 225 mAhg−1. Ex situ X-ray diffraction studies confirmed that (de) intercalation phenomena follows a solid-solution electrochemical reaction mechanism. As demonstrated, the reversibility and capacity utilization of this V4O9 is found to be superior to battery grade, micron-sized V2O5 cathodes in lithium cells.